Studies on variability in Alternaria alternata (Kessler) causing leaf blight of Isabgol (Plantago ovata) (SAARC Journal of Agriculture, 2015)
All the five isolates of Alternaria alternata isolated from different agro climate zone of Rajasthan were tested for their variability in terms of cultural, conidial, pathogenic characteristics and toxin production. All the five isolates differed in cultural characters i.e. dark black colored and very fast mycelial growth with smooth margins (90.00 mm), light black with white at centre and fast growing (80.00 mm), dark brown and medium mycelium growth with smooth margins (75.00 mm), black colored, medium flat mycelial growth with smooth margins (68.00 mm) and white with slightly black in colour with slow mycelial growth (65.00 mm) were observed in Aa-1, Aa-2, Aa-3, Aa-4 and Aa-5 respectively. The variability in conidial morphology of five different isolates was simple, septate, pale to dark brown in colour, often geniculate with one conidial scar. In respect of pathogenic variability, showed significant variations in terms of disease intensity and incubation periods. The isolates Aa-1 was highly pathogenic on Isabgol cv. RI-89 under artificial inoculation conditions showing 52.12% disease intensity followed by Aa- 3 ,Aa-2, Aa-4 and Aa-5 isolates. The variability in toxin production was reflected in terms of time taken in inducing wilting symptoms of Isabgol cuttings. Isolate Aa-1 was highly toxic followed by isolates Aa-2, Aa-3, Aa-4 and Aa-5. DOI: http://dx.doi.org/10.3329/sja.v12i2.21918 SAARC J. Agri., 12(2): 63-70 (2014)